Major Sociocultural Trends Shaping the Contemporary World. - Yeganeh, K. H. (Business Expert Press, 2017)
The current volume offers a concise and analytical portrait of the contemporary world. The author encompasses concepts and theories from multiple disciplines notably sociology, anthropology, international relations, and economics to examine the major sociocultural transformations of the modern world, their underlying causes, and their consequences. The volume is organized in 10 chapters dealing with a variety of topics including global demographic trends, globalization, culture, foreign affairs, emerging markets, environmental degradation, global security, global health, large corporations, and economic inequality. Each chapter is divided into separate sections examining the accompanying themes. This book is a valuable reference for managers and business leaders, students, policy makers, and all those who are interested in acquiring a better understanding of the sociocultural trends that are shaping our world.